Comparison of rocuronium-induced neuromuscular blockade in second trimester pregnant women and non-pregnant women. (May 2018) - Jun, I.J.; Jun, J.; Kim, E.M.; Lee, K.Y.; Kim, N.; Chung, M.H.; Choi, Y.R.; Choi, E.M.
Highlights: We compared the onset and duration of rocuronium in pregnant and non-pregnant women. The onset time of rocuronium did not differ significantly between the two groups. The duration of rocuronium was significantly longer in second trimester pregnancy. We hypothesize that differences are due to a relative reduction in liver blood flow. Abstract: Background: This study set out to compare the onset and duration of rocuronium-induced neuromuscular blockade in second trimester pregnant women and non-pregnant women receiving general anesthesia. Methods: Forty-seven pregnant (Group P) and forty-seven non-pregnant (Group C) women were enrolled. Anesthesia was induced with propofol 2.0 mg/kg and rocuronium 0.6 mg/kg, and neuromuscular blockade was assessed with an accelerometric sensor using train-of-four stimulation (TOF-Watch® SX). Tracheal intubation was performed at maximum depression of the first twitch (T1) and anesthesia was maintained with sevoflurane 1.5–2.5% and 50% oxygen in air. We recorded the times to maximum T1 depression and 5% and 25% T1 recovery, as well as the mean arterial pressure and heart rate at baseline, injection of rocuronium, intubation, and 5% and 25% T1 recovery. Results: The onset of rocuronium-induced neuromuscular blockade (time to maximum T1 depression) did not differ significantly between the groups. The duration (time to 25% T1 recovery) was significantly longer in Group P than in Group C (45.7 ± 12.9 min vs 40.6 ± 10.4 min, P <0.037). During the recovery period from the blockade, the mean arterial pressure was significantly lower in Group P than in Group C. Conclusion: Our data showed that the rocuronium-induced neuromuscular blockade did not significantly differ in onset but lasted significantly longer in second trimester pregnant women compared with non-pregnant women.